(untitled) (Research, Society and Development, 2021)
The objective of this research was to investigate the existence of a forecast for the development of competences for the prescription of medicines by nurses in the Pedagogical Course Projects (PPC) of the Nursing course of Higher Education Institutions in the public and private network of Campina Grande-PB. A qualitative study with a descriptive and documentary approach is proposed. The study was carried out in the city of Campina Grande-PB, together with higher education institutions that have the Nursing Undergraduate course in their teaching matrix. The collection took place through two operational stages: analysis of all PPC, the second was a semi-structured interview, using a previously established and flexible script with the course coordinators. The PPCs of the investigated institutions do not address curricular content/components to develop in the student competences for the prescription of medicines and that institutions face challenges in readjusting the pedagogical projects after the redemocratization of teaching. It is necessary that course coordinators and professors develop means to readjust the PPC in accordance with what the SUS advocates to promote in students a critical and reflective view focused on their field of action.